Carbon structures obtained from acetylene in a continuous current abnormal glow. (November 2019) - Alvarez, B; Sarmiento-Santos, A; Hernández, Y
Abstract: Carbon is the great constituent of all organic matter and a key element of the compounds that make up the enormous and very complex discipline of organic chemistry. It was already known in antiquity to be obtained as a by-product of the incomplete combustion of organic materials. At present the properties of this atom constitutes a potential source for research due to its promising application in nanotechnology and new materials because of its unique mechanical, electrical and optical properties. Carbon has several structural configurations that are known as allotropes, these allotropes have the same basic component, but its molecular conformation is different. Other elements of the fourth column of the periodic table such as silicon, germanium and tin have characteristics similar to those of carbon, however, this is unique in the variety of its allotropes. The different allotropes of carbon can be produced, among other methods, by the chemical vapor deposition method, however, the energy cost of this type of growth is relatively high. Another technique that would allow to obtain deposits of carbon in the laboratory is the plasma of the glow discharge of direct current in abnormal regime, which also offers a wide range of applications in plasmo-chemistry and in the thermochemical treatment of materials. The application of the abnormal glow discharge in the deposition of synthetic materials is a recent technique that represents a decrease in the time and in the energy consumption of the process, because the heating is carried out directly by the bombardment of the ions and neutral atoms on the surface of the cathode where the sample is usually located. The technique of abnormal glow discharge was used in this work with the objective of studying the possibility of formation of carbon deposits, in a copper substrate, from an atmosphere of argon, hydrogen and acetylene. Thus, in the temperature of 600 °C, deposits of graphite, graphene and an acetylene polymer compound were obtained. These were identified by infra-red spectrometry and Raman spectrometry.